Diversity of the genus Seira (Collembola: Entomobryidae: Seirinae) in the Fynbos and Southern Afrotemperate forest - Liu, Wing Pui Amy (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.